PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA SMP BERBASIS PENDEKATAN SAINTIFIK DENGAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Rohmatus Syafiah; Tukiran Tukiran; Fida Rachmadiarti (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research aimed to describe the teaching materials feasibility of IPA based on scientific approach with guided inquiry learning model. This research had been done in three phases, that are creating the teaching materials, validating and doing  revision, and verifying them at learning activity in class with one group pretest-posttest design. Techniques for collecting data was conducted through questionnaires, validation, observation, and test. Techniques for analyzing data used descriptive qualitative. The result of research showed that (1) the feasibility of teaching materials based on scientific approach with guided inquiry learning model of IPA that consist of syllabus,  lesson plan, student book, student worksheet and  the learning outcome test gained 4.89; 4.72; 4.81; 4.79; and 4.51 respectively that are categorized as valid. (2) The implementation of this lesson plan at two meetings in VII-A and VII-B class is categorized as good with average minimal scores 4.00 and got 94% in minimal percentage of agreement aspect; (3) Working in a group was the most dominant student activity at two meetings at VII-A and VII-B classes with average frequency of two meetings, observed are 19 and 10 times (VII-A class), and 18 and 10 times (VII-B class); (4) The learning outcomes that can be analyzed by calculating classical masteries at the first and second meetings on multiple choice and essay are 95.5%; 100%; 91%; 95% (VII-A class); and 91%; 86%; 91%; and 91% (VII-B class) respectively, and (5) Students gave the positive response to the learning process using teaching materials of IPA based on scientific approach with guided inquiry model with average score to be 3.3 (VII-A class) and 3.4 (VII-B class). Based on the result of the analyzed data, it can be concluded that the teaching materials of IPA based on scientific approach with guided inquiry model which had been developed was feasible to be used. Tujuan penelitian ini untuk mendeskripsikan kelayakan perangkat pembelajaran IPA SMP berbasis pendekatan saintifik dengan model pembelajaran inkuiri terbimbing. Penelitian ini dilaksanakan dalam tiga tahap, yaitu tahap mengembangkan perangkat pembelajaran, tahap validasi dan revisi, dan tahap uji coba dalam pembelajaran di kelas dengan menggunakan rancangan one group pretest-posttest design. Teknik pengumpulan data dengan angket, validasi, pengamatan, dan tes. Teknik analisis data menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa: (1) Kelayakan perangkat pembelajaran yang terdiri dari silabus, RPP, buku siswa, LKS, dan tes hasil belajar masing-masing diperoleh hasil 4,89; 4,72; 4,81; 4,79; dan 4,51 dengan kriteria valid. (2) Keterlaksanaan RPP pada dua pertemuan di kelas VII-A dan VII-B mendapatkan kriteria baik dengan skor rata-rata minimal 4,00 dan rata-rata persentase kesepakatan antara dua pengamat minimal 94%; (3) Frekuensi aktivitas siswa yang paling dominan pada dua pertemuan di kelas VII-A dan VII-B adalah bekerja dalam kelompok dengan frekuensi pengamatan rata-rata pada kedua pertemuan berturut-turut 19 dan 10 kali (kelas VII-A), dan 18 dan 10 kali (kelas VII-B) (4) Hasil belajar siswa yang dilihat dari  ketuntasan klasikal pada pertemuan pertama dan kedua pada soal PG dan uraian berturut-turut sebesar 95,5%; 100%; 91%; 95% (kelas VII-A); dan 91%; 86%; 91%; dan 91% (kelas VII-B), dan (5) Respon positif siswa terhadap pembelajaran IPA berbasis pendekatan saintifik dengan model pembelajaran inkuiri terbimbing dengan nilai rata-rata 3,3 (kelas VII-A) dan 3,4 (kelas VII-B). Berdasarkan hasil analisis data, diperoleh kesimpulan bahwa perangkat pembelajaran IPA berbasis pendekatan saintifik dengan model pembelajaran inkuiri terbimbing yang telah dikembangkan layak untuk digunakan.